2019
DOI: 10.3389/fpsyg.2019.00299
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Spatial Changes in Bimodal and Uni-Modal To-Be-Ignored Stimuli and How They Affect Short-Term Memory Processes

Abstract: This study examines the potential vulnerability of short-term memory processes to distraction by spatial changes within to-be-ignored bimodal, vibratory, and auditory stimuli. Participants were asked to recall sequences of serially presented digits or locations of dots while being exposed to to-be-ignored stimuli. On unexpected occasions, the bimodal to-be-ignored sequence, vibratory to-be-ignored sequence, or auditory to-be-ignored sequence changed their spatial origin from one side of the body (e.g., ear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…can result in higher accuracy and new findings. For instance, Marsja et al (2019) found that changes in bimodal stimuli (both visual and auditory) conveyed a shift in the performance of spatial and verbal short-term memory tasks while changes in visual or auditory stimuli individually did not lead to a significant shift in the performance of the mentioned tasks [27]. This can be easily achieved by the aid of our proposed system, by sending the markers indicating the onset, offset, and other information related to multiple stimuli in different streams simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…can result in higher accuracy and new findings. For instance, Marsja et al (2019) found that changes in bimodal stimuli (both visual and auditory) conveyed a shift in the performance of spatial and verbal short-term memory tasks while changes in visual or auditory stimuli individually did not lead to a significant shift in the performance of the mentioned tasks [27]. This can be easily achieved by the aid of our proposed system, by sending the markers indicating the onset, offset, and other information related to multiple stimuli in different streams simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…can result in higher accuracy and new findings. For instance, Marsja et al (2019) found that changes in bimodal stimuli (both visual and auditory) conveyed a shift in the performance of spatial and verbal short-term memory tasks, while changes in visual or auditory stimuli individually did not lead to a significant shift in the performance of the mentioned tasks [27].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In future, this platform can be expanded for multimodal-multisensory experiments that involve different human senses (e.g., tactile, hear, smell, taste, etc.). Applying OpenSync to different human senses will improve accuracy and is likely to advance our knowledge of human behavior [35]. For this purpose, the state-of-the-art deep learning models are powerful tools that have recently been used for combining and analyzing data from multiple sources together [36].…”
Section: Summary and Future Workmentioning
confidence: 99%